Production of fructo-oligosaccharides by Aspergillus ibericus and their chemical characterization. (March 2018) - Nobre, C.; Alves Filho, E.G.; Fernandes, F.A.N.; Brito, E.S.; Rodrigues, S.; Teixeira, J.A.; Rodrigues, L.R.
Abstract: A great demand for prebiotics is driving the search for new sources of fructo-oligosaccharides (FOS) producers and for FOS with differentiated functionalities. In the present work, FOS production by a new isolated strain of Aspergillus ibericus was evaluated. The temperature of fermentation and initial pH were optimized in shaken flask to yield a maximal FOS production, through a central composite experimental design. FOS were produced in a one-step bioprocess using the whole cells of the microorganism. The model (R 2 = 0.918) predicted a yield of 0.56, experimentally 0.53 ± 0.03 gFOS .ginitial sucrose −1 was obtained (37.0 °C and a pH of 6.2). A yield of 0.64 ± 0.02 gFOS .ginitial sucrose −1 was obtained in the bioreactor, at 38 h, with a content of 118 ± 4 g.L −1 in FOS and a purity of 56 ± 3%. The chemical structure of the FOS produced by A. ibericus was determined by HPLC and NMR. FOS were identified as 1-kestose, nystose, and 1 F -fructofuranosylnystose. In conclusion, A. ibericus was found to be a good alternative FOS producer. Highlights: Aspergillus ibericus is able to produce fructo-oligosaccharides (FOS). A temperature of 37.0 °C and pH 6.2 were found to maximize FOS production. FOS fermentation yielded 0.64 gFOS .gSucrose −1 with 118 g.L −1 concentration and 56% purity. FOS were identified as 1-kestose, nystose, and 1 F -fructofuranosylnystose.